Research of Healthy Behavior at Faculty of Economic Sciences' sport sciences' students at the University of Debrecen - Koroknay, Zsuzsa; Pfau, Christa (International Journal of Engineering and Management Sciences, 2019)
Nowadays the healthy lifestyle is getting more and more attention, thanks to emerging health trends. The review of the literature summarizes the latest results of research on two aspects of healthy behavior. In our primary research, we measured the sporting and dietry habits of sport sciences’ students at University of Debrecen. In the case of sporting habits, we asked the students about the frequency and motivation of sports. In the other hand we asked them about their dietary habits about the frequency and amount of vegetable, fruit and fluid consumption. After the evaluation of survey we can say that the 70% of respondents are satisfied with their physical condition. We can tell about the frequency of vegetable and fruit consumption is that the 15-20% of students eat vegetables and / or fruits daily. However, it can be said about the fluid intake of students that seventysix percent of them are consuming fluid daily.